The role of immunohistochemical markers in detecting Helicobacter Pylori - Daoud, Ali Kamel (Latakia University Journal -Medical Sciences Series, 2020)
Helicobacter pylori is one of the most common bacterial pathogens that affect humans. It causes chronic gastritis in its active and inactive forms and has an important role in various gastric disorders . Gastric endoscopical biopsy is the main diagnostic method for detecting H. pylori. This study aims to find the best methods for detecting H. pylori by using IHC markers and comparing it with the modified Giemsa stain which is routinely used in laboratories. The study was conducted on 170 gastric biopsies that were taken by upper gastrointestinal endoscopy and received at the department of pathology in Tishreen University Hospital in Lattakia. Sections of the samples were stained with H&E, modified Giemsa stains, and HP IHCl marker. The histological study determined the patterns and degrees of gastritis. H. pylori-positive cases were identified using Giemsa staining and IHC markers in all forms of gastritis. The study showed that the number of positive cases detected with IHC was higher by 36% (60 cases more) than the number of cases stained with modified Giemsa. When assessing these cases, it was found that H. pylori might present with a few small oval or coccoid forms and it could be scattered in uncommon sites which prevented it from being detected with routine Giemsa stain. The study concluded the necessity of using IHC markers in the diagnosis of H. pylori in gastric biopsies that showed histological signs of inflammation with negative H.pylori results when stained with modified Giemsa stain. الملتوية البوابية هي من أكثر الجراثيم التي تصيب البشر , تسبب التهابات المعدة المزمنة بشكليها الفعالة وغير الفعالة ولها دور هام في مختلف اعتلالات المعدة من قرحات , حؤول معوي , عسر تصنع , لمفوما معدية , وتشكل عامل خطورة رئيسي في حدوث السرطانات الغدية . الخزعة المعدية التنظيرية هي الوسيلة الرئيسية لكشف الملتوية البوابية في مخاطية المعدة . غيمزا المعدل المتبع بشكل روتيني في أغلب المخابر . أجريت الدراسة على 170 خزعة معدية مأخوذة بالتنظير الهضمي العلوي الواردة الى مخبر التشريح المرضي في مشفى تشرين الجامعي باللاذقية. لونت مقاطع من العينات بـ H&E وبملون غيمزا المعدل وبالواسم المناعي HP . حددت بالدراسة النسيجية أنماط الالتهابات المعدية ودرجاتها . حددت الحالات الإيجابية لوجود الملتوية البوابية بتلوين غيمزا وبالتلوين المناعي النسيجي عند كل شكل من أشكال الالتهابات المعدية. بينت الدراسة أن الحالات الإيجابية للملتوية البوابية بالواسم المناعي تزيد عن ملون غيمزا 60 حالة بنسبة 36% من الحالات المدروسة . لدى تقييم هذه الحالات تبين أن الملتوية البوابية تأخذ أشكال شاذة مكورة, بيضوية صغيرة جدا أو تكون نادرة جدا أو متوضعة في أماكن غير مألوفة مما سبب فشل اكتشافها بملون غيمزا. خلصت الدراسة الى ضرورة استعمال التلوين المناعي النسيجي في تشخيص الملتوية البوابية على الخزع المعدية التي تبدي وجود علامات نسيجية التهابية وسلبية لوجود الملتوية البوابية حسب تلوين غيمزا.